2022
DOI: 10.1002/mar.21760
|View full text |Cite
|
Sign up to set email alerts
|

Influencers' “organic” persuasion through electronic word of mouth: A case of sincerity over brains and beauty

Abstract: Despite the growing importance of influencers' word‐of‐mouth through audiovisual content, little is known about its effect on consumers' brand evaluation, purchase intentions, and decisions. Drawing on Ohanian's source credibility framework, we conducted two studies across different influencers, product categories, and respondents' gender and tested the hypotheses using covariance‐based and partial least square structural equation modeling. Study 1 focuses on a mega‐influencer of cosmetic and beauty brands and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 97 publications
(213 reference statements)
1
32
0
Order By: Relevance
“…Confirming our Hypotheses 2a, participants more frequently chose the right snack when it was advertised with a celebrity compared to when it was advertised with a Noncelebrity endorser ( b = −0.31, z = −3.20, p = 0.0013) or when it was presented alone ( b = −0.33, z = −2.80, p = 0.006; Figure 3a). A recent study has shown that source attractiveness predicts consumer choice (Filieri et al, 2022). Thus, we considered the possibility that this result might be explained by source attractiveness, rather than high social status, if celebrities are perceived as more attractive than non‐celebrities.…”
Section: Resultsmentioning
confidence: 99%
“…Confirming our Hypotheses 2a, participants more frequently chose the right snack when it was advertised with a celebrity compared to when it was advertised with a Noncelebrity endorser ( b = −0.31, z = −3.20, p = 0.0013) or when it was presented alone ( b = −0.33, z = −2.80, p = 0.006; Figure 3a). A recent study has shown that source attractiveness predicts consumer choice (Filieri et al, 2022). Thus, we considered the possibility that this result might be explained by source attractiveness, rather than high social status, if celebrities are perceived as more attractive than non‐celebrities.…”
Section: Resultsmentioning
confidence: 99%
“…, 2007; Fernandes et al. , 2022; Filieri et al ., 2023). Individuals perceive that they get either accepted or rejected by their peer groups based on their public appearances (Smith et al.…”
Section: Hypotheses Formulationmentioning
confidence: 99%
“…Extant research shows that perceived social acceptance is a predictor of the feeling of personal happiness (Mashili and Heydari, 2015) and subjective well-being (Smith, 1979;Arslan, 2018). Most individuals believe that appearance is an important factor that predicts social acceptance (Siperstein et al, 2007;Fernandes et al, 2022;Filieri et al, 2023). Individuals perceive that they get either accepted or rejected by their peer groups based on their public appearances (Smith et al, 2021).…”
Section: Consumer Cynicism Attenuating Brand Happinessmentioning
confidence: 99%
“…Compared to comments, ratings are simpler and can therefore be more readily processed by other consumers with less cognitive effort (Sparks & Browning, 2011). Given that this information often originates from those who are personally known by or share similar interests with the receiver, eWOM tends to be regarded as more reliable than formal marketing channels (Babić Rosario et al, 2020; Bazi et al, 2020; Filieri et al, 2023). Yet, eWOM behaviors may enable positive brand messages to be spread among consumers, thereby, strengthening the brand's image and increases in purchase intentions (Ismagilova et al, 2020; Marder et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Despite this initial reluctance, such brands now regularly use social media to deliver entertainment, interaction, trendiness, customization, and WOM (Kim & Ko, 2012). In fact, visual platforms like Instagram or YouTube offer opportunities for visual extensions of particular benefit to luxury fashion brands (Filieri et al, 2023; Sokolova & Kefi, 2020).…”
Section: Introductionmentioning
confidence: 99%